Eksistensi Cinta Lagu Saat Kau Telah Mengerti Karya Virgoun dalam Perspektif Semiotika - Siti Nurafriyani (Lingua Franca, 2024)
This article discusses the existence of love expressed in the song "Saat Kau Sudah Mengerti" by Virgoun. This article aims to: 1) Identify Denotative and Connotative Meanings, 2). Explore Moral Values and Messages, 3). Explain Intergenerational Relevance. This song represents the love and support of parents that endures beyond their physical presence, while reminding children about the importance of courage and integrity in living life. The results of this article show three main themes: 1) Parental love and attention that are often only understood by children in the future, 2) the importance of children's independence and courage even though their life choices differ from their parents' expectations, and 3). The continuity of values passed down between generations is the foundation of children's lives in the future. The lyrics of this song describe the role of parents as loving guides, even though they sometimes seem harsh in the eyes of children. The lyrics of the song "Saat Kau Sudah Mengerti" conclude about the deep emotional relationship between parents and children, with the main message about unconditional love and parental sacrifice in shaping children's characters. Semiotic analysis shows that these lyrics emphasize the importance of independence, courage, and integrity for children facing life's realities. However, this is often only understood by children later in life. Furthermore, the song depicts the continuity of life values passed down from parents to the next generation, emphasizing the role of parents as loving guides and supporters.